3-dimensional virtual reality application in education to improve student learning / Siti Hazyanti Mohd Hashim - Mohd Hashim, Siti Hazyanti (2022)
The use of virtual reality (VR) technology in learning has been emerging in the past few years. The use of VR involving 3-Dimensional (3D) VR is limited. There is a need to explore 3D VR in a dynamic physical application. 3D VR is able to immerse an individual in a simulated environment created to be realistic and with meaningful goals. The potential impact is an improved outcome of learning among students. It may also reduce the cost of education as students can learn by themselves. The platform created will also serve as an access to the technology for teachers, lecturers and parents. The objective of the application is to design a 3D VR module for student learning and to evaluate the effectiveness of 3D VR in education learning. The novelty is, the use of 3D VR is currently not a conventional practice in education and the learning concept in this project is novel for both students and lecturers.